X-ray imaging of 30 year old wine grape wood reveals cumulative impacts of rootstocks on scion secondary growth and Ravaz index. Issue 1 (7th October 2022) - Migicovsky, Zoë; Quigley, Michelle Y; Mullins, Joey; Ali, Tahira; Swift, Joel F; Agasaveeran, Anita Rose; Dougherty, Joseph D; Grant, Brendan Michael; Korkmaz, Ilayda; Malpeddi, Maneesh Reddy; McNichol, Emily L; Sharp, Andrew W; et al.
Summary: Annual rings from 30 year old vines in a California rootstock trial were measured to determine the effects of 15 different rootstocks on Chardonnay and Cabernet Sauvignon scions. Viticultural traits measuring vegetative growth, yield, berry quality, and nutrient uptake were collected at the beginning (1995 to 1999) and end (2017 to 2020) of the lifetime of a vineyard initially planted in 1991 and removed in 2021. X-ray Computed Tomography (CT) was used to measure ring widths in 103 vines. Ring width was modeled as a function of ring number using a negative exponential model. Early and late wood ring widths, cambium width, and scion trunk radius were correlated with 27 traits. Modeling of annual ring width shows that scions alter the width of the first rings but that rootstocks alter the decay of later rings, consistently shortening ring width throughout the lifetime of the vine. Ravaz index, juice pH, photosynthetic assimilation and transpiration rates, and instantaneous water use efficiency are correlated with scion trunk radius. Ultimately, our research indicates that rootstocks modulate secondary growth over years, altering physiology and agronomic traits. Rootstocks act in similar but distinct ways from climate to modulate ring width, which borrowing techniques from dendrochronology, can be used to monitor both genetic and environmental effects in woody perennial crop species.